Persepsi Peserta Didik Terhadap Regulasi Sekolah Dalam Meminimalisir Penyimpangan Perilaku di SMK Sasmita Jaya 2 Pamulang - Abi Robian; Herdi Wisman Jaya (Jurnal Pendidikan Kewarganegaraan, 2026)
This study aims to examine students' perceptions of school regulations and their effectiveness in minimizing behavioral deviations at SMK Sasmita Jaya 2 Pamulang. The research is motivated by the persistence of student misconduct—such as tardiness, dress code violations, and bullying—despite the enforcement of strict school rules. A descriptive quantitative method was used, employing a survey approach to gather data from students. The study focuses on three main objectives: (1) identifying students' perceptions of school regulations, (2) analyzing the effectiveness of these regulations in reducing deviant behavior, and (3) determining the factors that influence such perceptions. The results of this study are expected to provide empirical contributions for the development of more adaptive, participatory, and responsive school regulations. Furthermore, the findings may serve as a valuable reference for school administrators in formulating policies that foster a safe, orderly, and conducive learning environment.